2016
DOI: 10.1186/s40064-016-3206-1
|View full text |Cite
|
Sign up to set email alerts
|

The choice of internal fixator for fractures around the femoral trochanter depends on area classification

Abstract: PurposeIn femoral trochanteric fractures, fractures whose fracture lines extend to the basal neck or to the subtrochanteric part have high instability. Area classification can identify such instable fractures. The best choices of internal fixators for femoral trochanteric fractures were investigated according to area classification.MethodsFemoral trochanteric fractures were investigated with respect to area classification. In area classification, the proximal femur is divided into 4 areas with 3 boundary lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Based on their preoperative X-ray and computed tomography, including 3-dimensional computed tomography, the orthopedic surgeon at each hospital classified the PFF according to the Area Classification method. [12,15] Because of proven high inter-rater reliability, the Area classification for each case was not done by multiple orthopedic surgeons. [12] Incomplete proximal femur fractures that can only be detected by magnetic resonance imaging were excluded from this study, and only cases diagnosed by X-ray and computed tomography were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Based on their preoperative X-ray and computed tomography, including 3-dimensional computed tomography, the orthopedic surgeon at each hospital classified the PFF according to the Area Classification method. [12,15] Because of proven high inter-rater reliability, the Area classification for each case was not done by multiple orthopedic surgeons. [12] Incomplete proximal femur fractures that can only be detected by magnetic resonance imaging were excluded from this study, and only cases diagnosed by X-ray and computed tomography were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Their mean age was 82 years (range, 26-108 years). The type of fracture was retrospectively evaluated using the area classification [4, 5] based on X-ray films and 3D-CT images.…”
Section: Methodsmentioning
confidence: 99%
“…It is also possible to detect fractures involving the subcapital area to the trochanteric or subtrochanteric region by using this classification. In addition, this classification is reliable and useful for selecting therapeutic strategies [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Long IMNs have advantages over short nails for treating unstable fracture types. Kijima et al [4] investigated failure rates according to area classifications, and they found that short nails should be considered for fractures extending above the trochanter, while long nails should be considered when fractures extend to the subtrochanteric part. The use of long IMNs is a standard technique for treating femoral diaphysial fractures, [5] where a nail must be inserted from the proximal cavity into the distal medullary cavity.…”
Section: Introductionmentioning
confidence: 99%